Coloniality as a Barrier to Climate Action: Hierarchies of Power in a Coal‐Based Economy. Issue 3 (2nd December 2022) - van Ryneveld, Tara Nair; Islar, Mine
Abstract: South Africa has a coal‐based energy system and extractive economy, largely responsible for its high emission levels relative to countries with similar GDP. This extractive, coal‐based economy began during British colonisation and today shows few signs of transitioning rapidly to limit climate change. This paper interrogates the role of coloniality in climate delay, given that colonisation is responsible for establishing fossil fuel dependence in South Africa. Combining theory on decolonisation, specifically colonial hierarchies of power, with a critical discourse analysis, this research uses interview and policy data to show how colonial power hierarchies can lead to climate delay in South Africa, through normalising emissions intensive development and silencing alternatives. In doing so, it highlights the need to recognise the colonial foundations of climate change and the potential for a coalition between decolonisation and climate action to motivate for radical change both in South Africa and at a global level.